The effect of five-finger hypnosis therapy on anxiety levels among patients with type 2 diabetes mellitus - Akhmad Danu Shafar Pradana; Deasti Nurmaguphita; Slamet Riyanto (JOURNAL OF Mental Health Concerns, 2026)
Background: Patients with Type 2 Diabetes Mellitus often experience psychological disorders, one of which is anxiety due to lifestyle changes and long-term treatment. Five-finger hypnosis therapy is a non-pharmacological intervention that combines relaxation and positive suggestion. Purpose: To determine the effect of five-finger hypnosis therapy on reducing anxiety levels in Type 2 Diabetes Mellitus patients. Method: A pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 respondents selected through purposive sampling. The research instrument used the Hamilton Anxiety Rating Scale (HARS). Data analysis used the Paired Sample T-Test. Results: The average anxiety score before the intervention was 16.87 (SD = 2.921) and decreased to 11.27 (SD = 3.523) after the intervention. Statistical test results showed a p-value of 0.000 (< 0.05). Conclusion: There is a significant effect of providing five-finger hypnosis therapy in reducing anxiety levels in Type 2 Diabetes Mellitus patients. Keywords: Anxiety; Five-Finger Hypnosis; Type 2 Diabetes Mellitus.